Characterization of Melioribacter roseus gen. nov., sp. nov., a novel facultatively anaerobic thermophilic cellulolytic bacterium from the class Ignavibacteria, and a proposal of a novel bacterial phylum Ignavibacteriae. (9th January 2013) - Podosokorskaya, Olga A.; Kadnikov, Vitaly V.; Gavrilov, Sergey N.; Mardanov, Andrey V.; Merkel, Alexander Y.; Karnachuk, Olga V.; Ravin, Nikolay V.; Bonch‐Osmolovskaya, Elizaveta A.; Kublanov, Ilya V.
Summary A novel moderately thermophilic, facultatively anaerobic chemoorganotrophic bacterium strain P3M‐2T was isolated from a microbial mat developing on the wooden surface of a chute under the flow of hot water (46°C) coming out of a 2775‐m‐deep oil exploration well (Tomsk region, Russia). Strain P3M‐2T is a moderate thermophile and facultative anaerobe growing on mono‐, di‐ or polysaccharides by aerobic respiration, fermentation or by reducing diverse electron acceptors [nitrite, Fe(III), As(V)]. Its closest cultivated relative (90.8% rRNA gene sequence identity) is Ignavibacterium album, the only chemoorganotrophic member of the phylum Chlorobi. New genus and species Melioribacter roseus are proposed for isolate P3M‐2T. Together with I. album, the new organism represents the class Ignavibacteria assigned to the phylum Chlorobi. The revealed group includes a variety of uncultured environmental clones, the 16S rRNA gene sequences of some of which have been previously attributed to the candidate division ZB1. Phylogenetic analysis of M. roseus and I. album based on their 23S rRNA and RecA sequences confirmed that these two organisms could represent an even deeper, phylum‐level lineage. Hence, we propose a new phylum Ignavibacteriae within the Bacteroidetes–Chlorobi group with a sole class Ignavibacteria, two families Ignavibacteriaceae and Melioribacteraceae and two species I. album and M. roseus. This proposal correlates with chemotaxonomic data and phenotypic differences of both organisms from other cultured representatives of Chlorobi. The most essential differences, supported by the analyses of complete genomes of both organisms, are motility, facultatively anaerobic and obligately organotrophic mode of life, the absence of chlorosomes and the apparent inability to grow phototrophically.